2000
DOI: 10.1109/3.842104
|View full text |Cite
|
Sign up to set email alerts
|

Influence of energy-transfer upconversion on the performance of high-power diode-end-pumped CW lasers

Abstract: The influence of energy-transfer upconversion (ETU) on the performance of diode-end-pumped lasers is studied by including ETU effects into the space-dependent rate equations. The dependence of ETU rates on the mode-to-pump size ratio and on the output mirror transmission is derived. Experiments for Nd : YAG and Nd : YVO 4 crystals are performed to validate the present model. It is found that the ETU process increases the sensitivity of the output power to the output mirror transmission but its influence on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Our experimental observation that we were unable to obtain lasing with a 50% output coupler is, therefore, attributed to the presence of upconversion. Similar effects due to energy-transfer upconversion have also recently been described in CW -doped lasers [13]. The main reason for the drop in output power at low reflectivity for the case where no upconversion is present is depletion of the ground state, leading to a smaller absorption efficiency.…”
Section: B Output Channels For Input Powermentioning
confidence: 65%
“…Our experimental observation that we were unable to obtain lasing with a 50% output coupler is, therefore, attributed to the presence of upconversion. Similar effects due to energy-transfer upconversion have also recently been described in CW -doped lasers [13]. The main reason for the drop in output power at low reflectivity for the case where no upconversion is present is depletion of the ground state, leading to a smaller absorption efficiency.…”
Section: B Output Channels For Input Powermentioning
confidence: 65%
“…On the basis of analysis above, it is suggested that the emission from ODCs might be caused by multistep energy transfer from NBOHCs to ODCs, the schematic of which is shown in Fig. 3c, thus the possible upconversion mechanism for anti‐Stokes emission above is interpreted to be energy transfer 24–26.…”
Section: Resultsmentioning
confidence: 99%
“…For a single transverse mode and an ideal four-level Nd-doped laser, we can write the rate equation of population densities in the upper laser level N (r, z) and the total laser photons number in the cavity Φ in the steady state as [12,14] dNr; z dt…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…A number of papers have shown that the influence of energy-transfer upconversion (ETU) may be a detrimental effect in Nd-doped lasers [8][9][10][11][12][13][14][15][16][17][18][19][20]. The ETU process involves two nearby ions in the 4 F 3∕2 upper laser level; one ion relaxes down to a lower-lying level and transfers its energy to the other ion, which thereby upconverts to a higher level.…”
Section: Introductionmentioning
confidence: 99%